Edukasi Kesehatan tentang Upaya Pencegahan dan Penanganan Aspirasi Benda Asing dan Kejang Demam pada Anak di Rumah - Erita Sitorus; I Made Mertajaya; Sri Melfa Damanik (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2021)
ABSTRACT The emergency problem of foreign body aspiration or choking and febrile seizure in Toddlers is a serious emergency condition in children if not treated immediately can be life threatening for child. Observation by caregiver especially parents are very importants way during the child’age period. Handling foreign body aspiration and febril seizures in pre hospital quickly and immediately can prevent number of incident morbidity and mortality for Toddlers. The purpose of this Study is to increase the knowledge and skills of parents about preventing and handling foreign body aspiration and febrile seizures in Toddlers at home. There are thirty mothers who have toddler children participated in this study. The method of this study is online health education via Zoom combinated with a quantitative survey. The results showed that there was asignificant difference between pre and post test values of mother knowledge after being given socialization (P<0,001). Health education activities to parents especially mother or care givers about preventing and handling foreign body aspiration and febrile seizures at home are one effective way to reduce morbidity and mortality of incident injury children in Indonesia. Keywords: Toddlers, Febrile seizure, chocking, role of mother